Rapid batch preparation method of tritium-neutron composite proliferation agent lead lithium titanate pellets

By using lead lithium titanate ceramic pellets in nuclear fusion reactors, using Pb to replace part of Ti, combined with polymer-assisted sedimentation method, the problems of tritium self-sustaining and low tritium proliferation rates in the prior art are solved, and efficient tritium proliferation efficiency and pellet preparation are achieved.

CN119841636APending Publication Date: 2025-04-18HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510050655.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve tritium self-sustaining in nuclear fusion reactors, and lithium-based ceramics, as tritium proliferation material, cannot meet the tritium self-sustaining needs of the fusion reactor.

Method used

By using lead lithium titanate (Li2PbxTi1-xO3) ceramic spheres, using Pb elements to replace Ti in part of Li2TiO3, combined with polymer-assisted sedimentation method, rapid batch preparation of lead lithium titanate ceramic spheres was achieved.

Benefits of technology

The number of neutrons and tritium proliferation ratio are improved, the tritium proliferation efficiency is enhanced, the problem of low tritium proliferation rate of lithium-based ceramics is solved, and the efficient preparation of lead lithium titanate ceramic spheres is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841636A_ABST
    Figure CN119841636A_ABST
Patent Text Reader

Abstract

The invention provides a method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets in batches. The method comprises the following steps: firstly, accurately controlling the ratio of Li2TiO3 to PbO powder, and carrying out ball milling to prepare lead lithium titanate ceramic powder; then, dispersing the powder, a polymerizable monomer and polyvinyl alcohol in deionized water, adding ammonium persulfate as an initiator, and carrying out ball milling to form ceramic slurry; then, dropwise adding the slurry into silicone oil by utilizing a peristaltic pump, and preparing a lead lithium titanate ceramic pellet blank through the polymerization effect of liquid drops and polymerizable monomers; and finally, heating the blank to 873-1073K in air, and sintering for 3-6 hours to obtain a finished product. The method aims at solving the problems that the Li2TiO3 tritium breeding rate is relatively low, and Pb cannot be independently used as a solid-state cladding neutron multiplier. Pb element is used for replacing part of element Ti without proliferation effect in Li2TiO3, so that the proliferation effect is improved. Meanwhile, kilogram-level preparation of the lead lithium titanate ceramic pellets is realized by adopting a polymer-assisted sedimentation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for rapidly preparing in batches tritium-neutron composite breeder lead lithium titanate (Li2Pb x Ti 1- x The invention discloses a method for preparing a tritium-neutron composite breeder lead lithium titanate sphere, which relates to the field of nuclear fusion engineering. Background Art

[0002] Nuclear fusion energy is regarded as an ideal choice to solve the energy dilemma of human beings in the future. Deuterium-tritium reaction is the easiest to achieve artificial nuclear fusion, but tritium does not exist in nature. It is produced by the nuclear reaction of lithium isotopes in the blanket with neutrons from the deuterium-tritium fusion reaction. Therefore, the problem of tritium self-sustaining must be solved to realize the engineering application and steady-state operation of fusion energy. The inherent thermal stability and chemical inertness of lithium-based ceramics give it unique advantages in safety performance and are regarded as a promising tritium breeder material. In the International Thermonuclear Experimental Reactor (ITER) and DEMO, the helium-cooled tritium breeder blanket (HCPB) is a commonly used design for tritium breeder blankets. However, due to the neutron loss in the fusion process, if only tritium breeder lithium ceramics are used in the blanket, the tritium breeding ratio (TBR) will be difficult to be greater than 1, and the goal of "tritium self-sustaining" of the fusion reactor cannot be achieved. In this case, neutron multiplier beryllium or beryllium-titanium alloy is needed to increase the number of neutrons to increase the reaction probability of neutrons reacting with Li, but this will significantly increase the complexity of the blanket structure. In the analysis of many studies, beryllium (Be) and lead (Pb) are considered to have the most suitable physical properties as neutron multipliers in the blanket. Beryllium has a relatively high melting point of 1287°C. Lead has a lower melting point of 327°C, so it is mainly used in liquid form, so Pb cannot be used alone as a solid blanket neutron multiplier. Although Be has a higher neutron multiplication efficiency than Pb, its main weakness is that its reserves in nature are limited, so the huge cost hinders the application of Be neutron multiplication function. In order to solve the problem of relatively low tritium multiplication rate inherent in Li2TiO3 and the problem that Pb cannot be used alone as a solid blanket neutron multiplier, under the premise of not affecting the lithium density, the present invention proposes to utilize the similarity in chemical properties between Pb and Ti, and the fact that Li2TiO3 and Li2PbO3 exhibit similar monoclinic crystal structures, and adopt the research idea of ​​using Pb element to replace a part of Ti, an element without multiplication effect in Li2TiO3, and realizes the kilogram-level preparation of lithium lead titanate (Li2PbxTi1-xO3) ceramic spheres by a polymer-assisted sedimentation method. Summary of the invention

[0003] In view of the above situation, it is necessary to provide a method for rapidly batch preparing tritium-neutron composite breeder lead lithium titanate pellets that solves at least one of the above problems, characterized in that it comprises the following steps:

[0004] Step 1: Prepare lithium lead titanate ceramic powder according to Li2Pb x Ti 1-x The ratio of Li, Ti and Pb elements in LiO3 is: Li2TiO3 powder and PbO powder are placed in a ball milling jar filled with anhydrous ethanol, and the mass fraction of Pb is controlled by controlling the mass of PbO powder and the mass fraction of Pb, and ball milling is performed to obtain the lead titanate lithium powder;

[0005] Step 2: preparing lead-lithium titanate ceramic slurry, dispersing the lead-lithium titanate powder, polymerizable monomer and polyvinyl alcohol in deionized water, ball-milling in a ball mill, and adding 1 wt.% of ammonium persulfate as an initiator to obtain the lead-lithium titanate ceramic slurry;

[0006] Step 3: preparing a lead-lithium titanate ceramic sphere embryo, adding the lead-lithium titanate ceramic slurry into silicone oil through a peristaltic pump, wherein the lead-lithium titanate ceramic slurry forms droplets during the falling process, and the droplets polymerize with a polymerizable monomer to obtain a lead-lithium titanate ceramic sphere embryo;

[0007] Step 4: Prepare lead-lithium titanate ceramic beads, heat the lead-lithium titanate ceramic beads embryo to 873-1073K in an air atmosphere, and sinter for 3-6 hours to obtain lead-lithium titanate ceramic beads.

[0008] Preferably, the step 1 further includes the following steps:

[0009] S11: Drying treatment: the lead lithium titanate ceramic powder is transferred to a beaker, and then placed in a 70°C oven for drying for 12 hours to evaporate all the anhydrous ethanol to obtain a dried powder. The dried powder is then added to a ball mill, and LiOH·H2O is added to the ball mill, with a ball-to-powder ratio of 10:1. Dry grinding is performed for 10 minutes to mix the powder evenly.

[0010] Preferably, the step S11 further includes the following steps:

[0011] S12: Sample analysis: scanning the composition of the lead lithium titanate ceramic powder using an X-ray diffractometer.

[0012] Preferably, in the step one, the ball milling parameters for grinding the lead lithium titanate ceramic powder are a rotation speed of 300 rpm, a ball-to-powder ratio of 10:1, and a ball milling time of 32 hours. After each ball milling for 30 minutes, the machine is stopped for 20 minutes to adjust the forward and reverse directions.

[0013] Preferably, in the step three, a polymer-assisted sedimentation method is used to prepare the lead-lithium titanate ceramic sphere embryo, and the equipment used includes: a slurry tank, a peristaltic pump, a harmonic oscillating wall, a glass-jacketed sedimentation kettle and a circulating heating system.

[0014] Preferably, in the step three, the droplets are formed through a drip nozzle, and the vibration frequency f of the drip nozzle is 80 to 250 Hz.

[0015] Preferably, the size of the lead lithium titanate ceramic sphere embryo is proportional to the droplet diameter.

[0016] Preferably, the diameter of the drip nozzle is 0.4-0.6 mm, and the diameter of the droplet is 1.2-1.8 mm.

[0017] Preferably, the polymerizable monomer in step 2 is prepared by mixing acrylamide and N,N-methylenebisacrylamide in a molar ratio of 5:1 and a Macklin reagent.

[0018] Preferably, the chemical formula of the lithium lead titanate ceramic ball is Li2Pb x Ti 1-x O3, wherein x=0-0.7, and the lead-lithium titanate ceramic spheres have a structure of Li2TiO3 and Li2PbO3 monoclinic crystal structure; the lead-lithium titanate ceramic spheres have an average diameter of 1.2mm-1.4mm, a sphericity of 1.018-1.063, a crushing load of 25.33-52.54N, and a relative density of 87.22-94.89%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a polymer assisted sedimentation device.

[0020] Figure 2 This is a scanning electron microscope image of Li2TiO3 material.

[0021] Figure 3 It is Li2Pb 0.3 Ti 0.7 Scanning electron microscope image of O3 ceramic material. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the following is a further detailed description of the rapid batch preparation method of the tritium-neutron composite breeder lead lithium titanate spheres of the present invention in combination with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0023] In the description of the present invention, unless otherwise specified, "multiple" means two or more; the terms "center", "longitudinal", "lateral", "up", "down", "left", "right", "inside", "outside", "front end", "rear end", "head", "tail", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third" and the like are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0024] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this utility can be understood by specific circumstances.

[0025] Below, combined with the attached Figures 1 to 3 The specific embodiment mainly compares Li2TiO3 and Li2Pb 0.3 Ti 0.7 The properties of the two materials O3 were studied and the influence of the mass fraction of Pb on the material properties was explored.

[0026] Step 1: According to Li2Pb x Ti 1-x The ratio of Li, Ti and Pb elements in O3 Li2TiO3 powder and PbO powder are placed in a ball mill filled with anhydrous ethanol. The mass fraction of Pb is controlled by controlling the mass of PbO powder. The assembly is completed under the argon atmosphere in the glove box. The ball mill is placed on a planetary ball mill for ball milling. The ball milling speed is 300rpm, the ball-to-powder ratio is 10:1, and the ball milling time is 32h. After each ball milling for 30min, the machine is stopped for 20 minutes to adjust the forward and reverse directions. The powder obtained by ball milling is transferred to a beaker, and then placed in an oven at 70℃ to dry for 12 hours. The anhydrous ethanol is completely evaporated to obtain a dried powder. LiOH·H2O is added according to the ratio of Pb and Ti to supplement the Li element ratio. The ball milling is continued for 10 minutes to make the powder evenly mixed.

[0027] Step 2: Sample analysis of lead-lithium titanate ceramic materials. Take an appropriate amount of lead-lithium titanate ceramic sample and grind it into particles of 2 to 3 μm. Use XRD to analyze the grain composition of the lead-lithium titanate ceramic sample, and use inductively coupled plasma atomic emission spectroscopy (ICP-AES) to analyze the chemical composition of the lead-lithium eutectic ceramic sample. The atomic molar ratios of Li, Pb, and Si / Ti in the particles are basically consistent with the atomic molar ratios of Li, Pb, and Si / Ti in the gel in step S1;

[0028] Step 3: The polymer-assisted precipitation method realizes the lithium lead titanate (Li2Pb x Ti 1-x O3) Preparation of kilogram-level ceramic balls. The mixed powder after ball milling is placed in a mortar for grinding. The ground powder and a certain amount of polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio of 5:1, Macklin reagent) and an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, ball milled in a ball mill for 60 minutes, and ammonium persulfate (West Asia reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. Acrylamide and N, N-methylenebisacrylamide form an organic network to make the balls have better sphericity and strength.

[0029] The whole device consists of a circulating heating system, a glass jacketed sedimentation kettle, a peristaltic pump and a simple harmonic swing wall. The glass jacketed sedimentation kettle is filled with high-viscosity silicone oil (1000cst and above) as a sedimentation medium. After the ball-milled ceramic slurry is dripped into the silicone oil through a peristaltic pump, the slurry can form high-sphericity droplets under the action of gravity, viscous resistance and surface tension during the falling process, and the spherical droplets have enough time to complete the polymerization of the polymerizable monomers to form gel spherical bodies.

[0030] Step 4: Sintering of lead titanate lithium ceramic spheres. The prepared sphere precursor is taken out, cleaned, dried, and then moved into a corundum crucible and calcined in a muffle furnace. The sintering parameters are that the sample is heated from room temperature to 873-1073K at a rate of 5°C / min. After sintering for 3-6 hours, it is cooled in the furnace to obtain the sintered Li2Pb x Ti 1-x The prepared pellet precursor was taken out, cleaned, dried, and then moved into a corundum crucible and calcined in a muffle furnace. The sintering parameters were that the sample was heated from room temperature to 873-1073K at a rate of 5°C / min, sintered for 3-6 hours, and then cooled in the furnace to obtain the sintered Li2Pb 0.3 Ti 0.7 O3 small ball.

[0031] like Figure 1 As shown, when the present invention adopts the polymer-assisted sedimentation method to prepare lead-lithium titanate ceramic beads, the system used includes: a peristaltic pump, a simple harmonic oscillating wall, a glass-jacketed sedimentation kettle and a circulating heating system. The lead-lithium titanate ceramic slurry is stored in the slurry tank, and the slurry tank is connected to the peristaltic pump and the simple harmonic oscillating wall in sequence through a PVC (polyethylene) pipe. The simple harmonic oscillating wall has a drip nozzle. The glass-jacketed sedimentation kettle is placed below the simple harmonic oscillating wall. Hot silicone oil is stored in the glass-jacketed sedimentation kettle.

[0032] The lead-lithium titanate ceramic sample is fully ground into particles of 1 to 2 μm to obtain lead-lithium titanate ceramic powder. The working process of the system is: the ground powder and a certain amount of polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio of 5:1, McLean reagent), an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, and the amount of polymerizable monomer is 2.5wt%, 5.5wt%, 7.1wt%, 9.5wt%, 11.8wt%, 13.9wt%, respectively, ball milled in a ball mill for 60 minutes, and ammonium persulfate (West Asia reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. One end of the peristaltic pump is immersed in the slurry in the slurry tank, the peristaltic pump is started, the slurry enters the peristaltic pump, and the speed of extracting the slurry is adjusted. Under the action of the simple harmonic oscillating wall, the slurry drips drop by drop into the glass jacketed sedimentation kettle; the circulating heating system is used to keep the silicone oil in the sedimentation kettle at a constant temperature (110°C), and the slurry slowly drips into the viscous hot medium to form spherical droplets. During the sedimentation process, polymerization occurs inside the droplets and finally forms precursor spheres.

[0033] Sintering of lithium lead titanate ceramic spheres. The prepared sphere precursor is taken out, cleaned, dried, and then moved into a corundum crucible and calcined in a muffle furnace. The sintering parameters are that the sample is heated from room temperature to 873-1073K at a rate of 5°C / min. After sintering for 3-6 hours, it is cooled in the furnace to obtain the sintered Li2Pb x Ti 1-x O3 ceramic balls. After taking them out, perform performance testing;

[0034] Take lead lithium titanate ceramic ball samples, use scanning electron microscopy (SEM) to analyze the sample surface and the microstructure inside after crushing, use XRD to analyze the sample grain composition, use Archimedes method to measure the sample density, use digital image analysis to measure the sphericity of the ball, and use static pressure method to test the size of the ball crushing load.

[0035] Analysis of lead-liquid titanate ceramic pellet samples: X-ray diffractometer (X, PertMPD, CuKα) was used to analyze the phase of the sintered ceramic pellets. The pellet samples needed to be crushed and ground into powders less than 100μm before testing. X-rays used CuKα, tube voltage 40kV, current 100mA, 2θ range: 10-80°, scanning speed: 10° / min. Scanning electron microscope (SU8000) was used to analyze its microstructure.

[0036] The diameter and sphericity of the spheres were measured using an optical microscopy measurement system. The density of the ceramic spheres was calculated based on the Archimedean principle at room temperature with anhydrous methanol as the immersion medium. The crushing load of a single sphere was measured on a constant speed compression mechanics testing machine with a compression rate of 50 to 200 μm min -1 , draw the load-displacement curve, take the maximum value of the load mutation as the crushing load of the ball, and do 10 groups in parallel to get the average value. The polymer-assisted sedimentation method was used to realize the x Ti 1-x O3) Preparation of kilogram-level lead titanate ceramic balls. The size of the lead titanate lithium ceramic balls is proportional to the droplet diameter. According to experimental analysis, when the vibration frequency f of the drip nozzle is in the range of 80-250Hz, the sphericity of the balls is better. In addition, the droplet diameter is also related to the viscosity of the slurry, the diameter of the drip nozzle, and the wettability between the slurry and the drip nozzle material. According to the experimental optimization of parameters such as solution ratio, drip nozzle diameter and vibration frequency, the average diameter of the prepared lead titanate lithium ceramic balls is 1.2mm-1.4mm, the sphericity is 1.018-1.063, the crushing load is 25.33-52.54N, and the relative density is 87.22-94.89%. At present, the yield of ceramic balls prepared by this method can reach 42-45g·h -1 , and the output can be further increased by adjusting the peristaltic pump flow, the number of nozzles and the diameter of the sedimentation kettle.

[0037] As the sintering temperature increases, the water in the sample evaporates continuously and the sample weight decreases continuously. The thermogravimetric / differential thermal analysis (TG–DTA) method is used to measure the curve of sample mass change with temperature, and the heating rate is 10℃·min-1.

[0038] Example 1

[0039] Preparation of lithium lead titanate ceramic materials. x Ti 1-xThe ratio of Li, Ti and Pb elements in O3 (x = 0) is as follows: Li2TiO3 powder is loaded into a ball mill filled with anhydrous ethanol, and the assembly is completed under an argon atmosphere in a glove box. The ball mill is placed on a planetary ball mill for ball milling. The ball milling speed is 300rpm, the ball-to-powder ratio is 10:1, and the ball milling time is 32h. After each ball milling for 30min, the machine is stopped for 20 minutes to adjust the forward and reverse directions. The powder obtained by ball milling is transferred to a beaker, and then placed in an oven at 70℃ to dry for 12 hours, and all the anhydrous ethanol is evaporated to obtain a dried powder.

[0040] Sample analysis of lead-lithium titanate ceramic materials. Take an appropriate amount of lead-lithium titanate ceramic sample and grind it into particles of 1 to 2 μm. Use XRD to analyze the grain composition of the lead-lithium titanate ceramic sample, and use inductively coupled plasma atomic emission spectroscopy (ICP-AES) to analyze the chemical composition of the lead-lithium titanate ceramic sample. The atomic molar ratios of Li, Pb, and Si / Ti in the particles are basically consistent with the atomic molar ratios of Li, Pb, and Si / Ti in the gel in step S1;

[0041] The polymer-assisted sedimentation method achieves the kilogram-level preparation of lead titanate lithium ceramic balls. The ball-milled mixed powder is placed in a mortar for grinding. The ground powder and a certain amount of polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio of 5:1, MacLean reagent) and an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, ball-milled in a ball mill for 60 minutes, and ammonium persulfate (West Asia reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. Acrylamide and N, N-methylenebisacrylamide form an organic network to give the balls better sphericity and strength.

[0042] This embodiment adopts Figure 1 The system shown. Figure 1 As shown, the polymer-assisted sedimentation method used in the present invention is used to prepare the lead lithium titanate ceramic ball system, and the system has been described in detail in the specific implementation method part.

[0043] The lead-lithium titanate ceramic sample is fully ground into particles of 1 to 2 μm to obtain lead-lithium titanate ceramic powder. The working process of the system is: the ground powder and a certain amount of polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio 5:1, McLean reagent), an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, ball-milled in a ball mill for 60 minutes, and ammonium persulfate (Xi'a ​​reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. One end of the peristaltic pump is immersed in the slurry in the slurry tank, the peristaltic pump is started, the slurry enters the peristaltic pump, the speed of extracting the slurry is adjusted, and under the action of the simple harmonic swing wall, the slurry is dripped into the glass jacket sedimentation kettle drop by drop; the circulating heating system is used to keep the silicone oil in the sedimentation kettle at a constant temperature (110°C), and the slurry is slowly dripped into the viscous hot medium to form spherical droplets. During the sedimentation process, polymerization occurs inside the droplets and finally forms precursor spheres.

[0044] Sintering of lead-lithium titanate ceramic spheres. The prepared sphere precursor is taken out, cleaned, dried, and then moved into a corundum crucible and calcined in a muffle furnace. The sintering parameters are that the sample is heated from room temperature to 873-1073K at a rate of 5°C / min. After sintering for 3-6 hours, it is cooled in the furnace to obtain the sintered Li2TiO3 ceramic spheres. After taking out, the performance is tested;

[0045] Analysis of lead-liquid titanate ceramic pellet samples: X-ray diffractometer (X, PertMPD, CuKα) was used to analyze the phase of the sintered ceramic pellets. The pellet samples needed to be crushed and ground into powders less than 100μm before testing. X-rays used CuKα, tube voltage 40kV, current 100mA, 2θ range: 10-80°, scanning speed: 10° / min. Scanning electron microscope (SU8000) was used to analyze its microstructure.

[0046] The diameter and sphericity of the spheres were measured using an optical microscopy measurement system. The density of the ceramic spheres was calculated based on the Archimedean principle at room temperature with anhydrous methanol as the immersion medium. The crushing load of a single sphere was measured on a constant speed compression mechanics testing machine with a compression rate of 50 to 200 μm min -1 , draw the load-displacement curve, take the maximum value of the load mutation as the crushing load of the ball, and do 10 groups in parallel to get the average value. The average diameter of the prepared lithium titanate ceramic balls is 1.2mm-1.4mm, the sphericity is 1.018-1.063, the crushing load is 14.49-35.58N, and the relative density is 83.73-92.59%. At present, the yield of ceramic balls prepared by this method can reach 42-45g·h -1In the experiment of preparing lead lithium titanate ceramic balls by polymer-assisted sedimentation method, the size of lithium titanate ceramic balls is proportional to the droplet diameter. The droplet diameter is related to the vibration frequency of the drip nozzle, the drip nozzle diameter, the drip nozzle diameter and the viscosity of the slurry. In this example, the vibration frequency f of the drip nozzle is 160Hz; the drip nozzle diameter is 0.5mm; the viscosity of the slurry is affected by the amount of polymerization monomer added, and the polymerization monomer content is 7.1wt%.

[0047] Example 2

[0048] Preparation of lithium lead titanate ceramic materials. x Ti 1-x O3 (x = 0.3) The ratio of Li, Ti and Pb elements. Li2TiO3 powder and PbO powder are placed together in a ball mill filled with anhydrous ethanol, and the assembly is completed under an argon atmosphere in a glove box. The ball mill is placed on a planetary ball mill for ball milling. The ball milling speed is 300rpm, the ball-to-powder ratio is 10:1, and the ball milling time is 32h. After each ball milling for 30min, the machine is stopped for 20 minutes to adjust the forward and reverse directions. The powder obtained by ball milling is transferred to a beaker, and then placed in a 70℃ oven for 12 hours to evaporate all the anhydrous ethanol to obtain a dried powder. LiOH·H2O is added according to the ratio of Pb and Ti to supplement the Li element ratio. Continue ball milling for 10 minutes to make the powder evenly mixed.

[0049] Sample analysis of lead-lithium titanate ceramic materials. Take an appropriate amount of lead-lithium titanate ceramic sample and grind it into particles of 1 to 2 μm. Use XRD to analyze the grain composition of the lead-lithium titanate ceramic sample, and use inductively coupled plasma atomic emission spectroscopy (ICP-AES) to analyze the chemical composition of the lead-lithium eutectic ceramic sample. The atomic molar ratios of Li, Pb, and Si / Ti in the particles are basically consistent with the atomic molar ratios of Li, Pb, and Si / Ti in the gel in step S1;

[0050] The polymer-assisted precipitation method has realized the x Ti 1-x O3) Preparation of kilogram-level ceramic balls. The mixed powder after ball milling is placed in a mortar for grinding. The ground powder and a certain amount of polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio of 5:1, Macklin reagent) and an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, ball milled in a ball mill for 60 minutes, and ammonium persulfate (West Asia reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. Acrylamide and N, N-methylenebisacrylamide form an organic network to make the balls have better sphericity and strength.

[0051] This embodiment adopts Figure 1 The system shown. Figure 1 As shown, the polymer-assisted sedimentation method used in the present invention is used to prepare the lead lithium titanate ceramic ball system, and the system has been described in detail in the specific implementation method part.

[0052] The lead-lithium titanate ceramic sample is fully ground into particles of 1 to 2 μm to obtain lead-lithium titanate ceramic powder. The working process of the system is: the ground powder and polymerizable monomer (acrylamide and N, N-methylenebisacrylamide molar ratio of 5:1, McLean reagent), and an appropriate amount of polyvinyl alcohol (analytical grade) are dispersed in deionized water, ball-milled in a ball mill for 60 minutes, and ammonium persulfate (Xi'a ​​reagent) with a monomer addition amount of 1wt.% is added as an initiator to obtain the required slurry. One end of the peristaltic pump is immersed in the slurry in the slurry tank, the peristaltic pump (3) is started, the slurry enters the peristaltic pump, the speed of extracting the slurry is adjusted, and under the action of the simple harmonic swing wall, the slurry is dripped into the glass jacket sedimentation kettle drop by drop; the circulating heating system is used to keep the silicone oil in the sedimentation kettle at a constant temperature (110°C), and the slurry is slowly dripped into the viscous hot medium to form spherical droplets. During the sedimentation process, polymerization occurs inside the droplets to finally form precursor spheres.

[0053] Sintering of lithium lead titanate ceramic spheres. The prepared sphere precursor is taken out, cleaned, dried, and then moved into a corundum crucible and calcined in a muffle furnace. The sintering parameters are that the sample is heated from room temperature to 873-1073K at a rate of 5°C / min. After sintering for 3-6 hours, it is cooled in the furnace to obtain the sintered Li2Pb 0.3 Ti 0.7 O3 ceramic balls. After taking them out, perform performance testing;

[0054] Analysis of lead-liquid titanate ceramic pellet samples: X-ray diffractometer (X, PertMPD, CuKα) was used to analyze the phase of the sintered ceramic pellets. The pellet samples needed to be crushed and ground into powders less than 100μm before testing. X-rays used CuKα, tube voltage 40kV, current 100mA, 2θ range: 10-80°, scanning speed: 10° / min. Scanning electron microscope (SU8000) was used to analyze its microstructure.

[0055] The diameter and sphericity of the spheres were measured using an optical microscopy measurement system. The density of the ceramic spheres was calculated based on the Archimedean principle at room temperature with anhydrous methanol as the immersion medium. The crushing load of a single sphere was measured on a constant speed compression mechanics testing machine with a compression rate of 50 to 200 μm min -1, draw the load-displacement curve, take the maximum value of the load mutation as the crushing load of the ball, and do 10 groups in parallel to get the average value. The average diameter of the prepared lithium lead titanate ceramic ball is 1.2mm-1.4mm, the sphericity is 1.018-1.063, the crushing load is 25.33-52.54N, and the relative density is 87.22-94.89%. At present, the yield of ceramic balls prepared by this method can reach 42-45g·h -1 .

[0056] In the experiment of preparing lead titanate lithium ceramic balls by polymer-assisted sedimentation method, the size of lead titanate lithium ceramic balls is proportional to the droplet diameter, and the droplet diameter is related to the vibration frequency of the drip nozzle, the drip nozzle diameter, the drip nozzle diameter and the viscosity of the slurry. In this example, the vibration frequency f of the drip nozzle is 160Hz; the drip nozzle diameter is 0.5mm; the viscosity of the slurry is affected by the amount of polymerization monomer added, and the polymerization monomer content is 7.1wt%.

[0057] The addition of Pb can refine the grains of the sintered material, and the loading of the material with Pb added is higher than that of the material without Pb added.

[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets in batches, characterized in that: The following steps are involved: Step 1: Prepare lithium lead titanate ceramic powder according to Li2Pb x Ti 1-x The ratio of Li, Ti and Pb elements in LiO3 is: Li2TiO3 powder and PbO powder are placed in a ball milling jar filled with anhydrous ethanol, and the mass fraction of Pb is controlled by controlling the mass of PbO powder and the mass fraction of Pb, and ball milling is performed to obtain the lead titanate lithium powder; Step 2: preparing lead-lithium titanate ceramic slurry, dispersing the lead-lithium titanate powder, polymerizable monomer and polyvinyl alcohol in deionized water, ball-milling in a ball mill, and adding 1 wt.% of ammonium persulfate as an initiator to obtain the lead-lithium titanate ceramic slurry; Step 3: preparing a lead-lithium titanate ceramic sphere embryo, adding the lead-lithium titanate ceramic slurry into silicone oil through a peristaltic pump, wherein the lead-lithium titanate ceramic slurry forms droplets during the falling process, and the droplets polymerize with a polymerizable monomer to obtain a lead-lithium titanate ceramic sphere embryo; Step 4: Prepare lead-lithium titanate ceramic beads, heat the lead-lithium titanate ceramic beads embryo to 873-1073K in an air atmosphere, and sinter for 3-6 hours to obtain lead-lithium titanate ceramic beads.

2. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate beads in batches as claimed in claim 1, characterized in that: The step 1 also includes the following steps: S11: Drying treatment: the lead lithium titanate ceramic powder is transferred to a beaker, and then placed in a 70°C oven for drying for 12 hours to evaporate all the anhydrous ethanol to obtain a dried powder. The dried powder is then added to a ball mill, and LiOH·H2O is added to the ball mill, with a ball-to-powder ratio of 10:

1. Dry grinding is performed for 10 minutes to mix the powder evenly.

3. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets as claimed in claim 2, characterized in that: The S11 further includes the following steps: S12: Sample analysis: scanning the composition of the lead lithium titanate ceramic powder using an X-ray diffractometer.

4. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets as claimed in claim 1, characterized in that: In the step 1, the ball milling parameters for grinding the lead lithium titanate ceramic powder are a rotation speed of 300 rpm, a ball-to-powder ratio of 10:1, and a ball milling time of 32 hours. After each ball milling for 30 minutes, the machine is stopped for 20 minutes to adjust the forward and reverse directions.

5. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets as claimed in claim 1, characterized in that: In the step three, a polymer-assisted sedimentation method is used to prepare a lead-lithium titanate ceramic sphere embryo, and the equipment used includes: a slurry tank, a peristaltic pump, a harmonic oscillating wall, a glass-jacketed sedimentation kettle and a circulating heating system.

6. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets as claimed in claim 5, characterized in that: In the step three, droplets are formed through a drip nozzle, and the vibration frequency f of the drip nozzle is 80 to 250 Hz.

7. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate beads in batches as claimed in claim 6, characterized in that: The size of the lead-lithium titanate ceramic sphere embryo is proportional to the droplet diameter.

8. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate beads in batches as claimed in claim 7, characterized in that: The diameter of the drip nozzle is 0.4-0.6 mm, and the diameter of the droplet is 1.2-1.8 mm.

9. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets as claimed in claim 1, characterized in that: The polymerizable monomer in the step 2 is prepared by mixing acrylamide and N,N-methylenebisacrylamide in a molar ratio of 5:1 and a Macklin reagent.

10. The method for rapidly preparing tritium-neutron composite breeder lead lithium titanate pellets in batches according to any one of claims 1 to 9, characterized in that: The chemical formula of the lithium lead titanate ceramic ball is Li2Pb x Ti 1-x O3, wherein x=0-0.7, and the lead-lithium titanate ceramic spheres have a structure of Li2TiO3 and Li2PbO3 monoclinic crystal structure; the lead-lithium titanate ceramic spheres have an average diameter of 1.2mm-1.4mm, a sphericity of 1.018-1.063, a crushing load of 25.33-52.54N, and a relative density of 87.22-94.89%.

Citation Information

Patent Citations

  • Lithium titanate ceramic ball tritium propagation material and preparation method thereof

    CN103183509A

  • Preparation method of tritium multiplication ceramic pellet in fusion reactor solid blanket

    CN108751975A